Russian-Chilean relations in the XIX-XX centuries - Sizonenko, Alexander (Iberoamerikanskie tetradi, 2016)
The article deals with the analysis of the formation of the Russian-Chilean relations and the contacts between the both countries in the XIX-XX centuries